CEO salary, personal characteristics, and firm performance in Chinese-listed firms: A cross-sectional econometric modeling approach - Wu, Ming-Lu (Journal of Management, Economics, and Industrial Organization, 2021)
This study examines the relationships among CEO salary, CEO personal characteristics (such as age, education, and gender), and firm performance. Based on the special phenomenon that female CEOs are much fewer than male CEOs in Chinese-listed firms, the current research aims to discover whether gender is a significant factor affecting firm performance and CEO salary. Cross-sectional econometric models are estimated using data from about 2,600 Chinese-listed firms in 2018 in this study. According to the findings, CEO gender is not significant enough to affect firm performance while female CEOs, although capable of playing the same roles as male CEOs, receive a lower level of salary than male CEOs on average, which leads to certain degree of gender discrimination in the CEO position in China’s listed firms. The findings of this study also have implications for further studies relating to CEO pay, financial performance, and gender discrimination.
Keywords: CEO salary; personal characteristics; firm performance; gender effect; listed firms; econometric models